2021
DOI: 10.3390/ijerph182010891
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Housing Environmental Attributes and Design Exposures and Psychoneuroimmunology Profile—An Exploratory Review and Analysis Paper in the Cancer Survivors’ Mental Health Morbidity Context

Abstract: Adult cancer survivors have an increased prevalence of mental health comorbidities and other adverse late-effects interdependent with mental illness outcomes compared with the general population. Coronavirus Disease 2019 (COVID-19) heralds an era of renewed call for actions to identify sustainable modalities to facilitate the constructs of cancer survivorship care and health care delivery through physiological supportive domestic spaces. Building on the concept of therapeutic architecture, psychoneuroimmunolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 315 publications
(334 reference statements)
0
9
0
Order By: Relevance
“…In terms of nutritional status, the prognostic nutritional index (PNI) and controlling nutritional status (CONUT) scores are associated with disease severity and have a predictive role in COVID-19 patient mortality [ 52 , 53 , 54 , 55 , 56 , 57 ]…”
Section: Introductionmentioning
confidence: 99%
“…In terms of nutritional status, the prognostic nutritional index (PNI) and controlling nutritional status (CONUT) scores are associated with disease severity and have a predictive role in COVID-19 patient mortality [ 52 , 53 , 54 , 55 , 56 , 57 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such a result, although limited in term of point increase on the specific subscales, may represent an encouraging cue to highlight, especially considering that our subject, being a young woman, a student, an oncological patient, and a competitive athlete, fell under all the socio-demographical categories most negatively impacted by the pandemic. Noteworthy, the aforementioned characteristics are well-demonstrated to be strongly related to depression and anxiety symptoms development [ 1 , 10 , 11 , 12 , 13 ]. In particular, concerning the depression state worsening, we could also hypothesize that individual session training, even though necessary to more quickly achieve the main goals and to minimize COVID-19 contagion risk, represents a methodological approach not easily accepted and appreciated by a young team sport athlete [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another target population deeply influenced by the COVID-19 pandemic has been the oncological. Cancer is a complex and multidimensional disease usually difficult to bear and manage in normal circumstances, and which may even become overwhelming in a stressful context such as the recent pandemic [ 10 , 11 ]. Among cancer patients, the clinicodemographic characteristic showing a significant association with higher psychophysical distress vulnerability is female gender [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Random-effects models will be used to pool study-specific effect size measures using the Paule and Mandel estimator for the between-study variance. 72 From our previous analysis on the topic, 39 we observed studies with multiple or single biomarker(s) reported at multiple time points. Therefore, we conduct subgroup analyses by length of follow-up: short-term (≤2 weeks), mid-term (>2 weeks to ≤6 months), and longterm (>6 months).…”
Section: Discussionmentioning
confidence: 99%
“…38 Interventions modifying the household environmental quality -air, artificial lighting and nature-trigger changes on the residents' inflammatory levels, particularly interleukin-6, CRP, high sensitivity-CRP, endothelial growth factor, granulocyte-colony stimulating factor, and Eotaxin. 39 This systematic review will examine the effectiveness of H-BE interventions modifying air quality, thermal comfort, non-ionising radiation, noise, nature and water on inflammatory biomarkers in community-dwelling adults. This study intends to provide the groundwork for future H-BE interventions as inflammation-targeting treatment in CS for potential consideration in general practice (Figure 1).…”
Section: Introductionmentioning
confidence: 99%